MASA PEMERINTAHAN ALI BIN ABI THALIB DARI TAHUN 655-660M - Pratama, Tegar Sidiq; Prayoga, Dian (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2023)
Ali bin Abi Talib was a friend of the prophet and Kholifah after the end of Ustman Bin Affan's caliphate. During the reign of Ali bin Abi Talib, he experienced a dynamic incident. One of these dynamics is the development of Muslims during the time of Caliph Ali bin Abi Talib in the field of development. This thesis will explain the reign of Ali Bin Abi Talib from 655-660 AD. The limitations of the study in this research are the final description of Ustman bin Affan's government, the dynamics of Ali bin Abi Talib's government and the development of Muslims during the time of Ali bin Abi Talib. The aim of this research is to find out the final picture of Ustman's reign, to know the dynamics of Ali bin Abi Talib's government and the development of Muslims during the time of Ali bin Abi Talib. The methodology used in writing this research is historical research methodology and researchers focus on library sources or library research, namely research that reveals facts through library data. The results of investigations from various scientific studies reveal that after the murder of Ustman bin Affan, the Muslim community experienced chaos due to the absence of a caliph, so with the coercion of the people and friends, Ali bin Abi Talib was appointed as the new caliph after Ustman bin Affan. The Muslim community during the time of Caliph Ali experienced several development, namely in the fields of military, development and education.